Jardins de Bagatelle. (München : Galerie Tanit, 1990)
Anderson, Curtis ; Baumgarten, Lothar ; Lüthi, Urs ; Koons, Jeff ; Mentor, Will ; Morandi, Giorgio ; Munoz, Juan ; Noland, Cady ; van Oost, Jan ; Pistoletto, Michelangelo ; Sasse, Jörg ; Spalletti, Ettore ; Steinbach, Haim ; Trockel, Rosemarie ; Wallace, Ian
Jardins de Bagatelle, Galerie Tanit, München, 1990
boek